PENGARUH TERPAAN TIKTOK “SECRET RECIPE” TERHADAP MINAT BELI STARBUCKS PADA MAHASISWA DI INDONESIA (Studi Kasus Video “Secret Recipe” @Decxymalvin di TikTok) (E-Jurnal Medium, 2022)
TikTok is a social networking application that is known as a place to do business, creating interesting content from various categories and attracting new users continuously to increase the existence of the application itself. A Starbucks barista with the TikTok account @Decxymalvin is one of the content providers who uses social media to promote knowledge. @Decxymalvin posts some fascinating content, including the debut of